Comet - Carl Sagan; Ann Druyan; SAGAN (Carl); DRUYAN (Ann) (New York Random House, 1985)
Documents the history of Halley's Comet and describes, in two hundred photographs and an informative text, the path of the comet and the astronomical details of its existence
Keywords: Halleys Comet; Astride